Silicon germanium : - Singh, Raminderpal (Wiley-Interscience, 2004)
This volume provides an excellent introduction to the SiGe BiCMOS technology, from the underlying device physics to current applications. But just as important is the window the text provides into the infrastructure–the process development, device modeling, and tool development.